Survival Outcomes of Radical Prostatectomy + Extended Pelvic Lymph Node Dissection and Radiotherapy in Prostate Cancer Patients With a Risk of Lymph Node Invasion Over 5%: A Population-Based Analysis - Chen, Junru; Ni, Yuchao; Sun, Guangxi; Zhu, Sha; Zhao, Jinge; Wang, Zhipeng; Zhang, Haoran; Zhu, Xudong; Zhang, Xingming; Dai, Jindong; Shen, Pengfei; Zeng, Hao (Frontiers in Oncology, 2020)
Purpose: We aimed to compare the efficacy of radical prostatectomy (RP) + extended pelvic lymph node dissection (ePLND) and radiotherapy (RT) in localized prostate cancer (PCa) patients with a risk of lymph node invasion (LNI) over 5%. Methods: The Surveillance, Epidemiology, and End Results (SEER) databases were used to identify patients with PCa from 2010 to 2014. Propensity score matching (PSM) was performed to balance baseline characteristics between patients in different treatment groups. Kaplan-Meier curves and Cox regression were used to assess the effects of treatments on cancer-specific survival (CSS) and overall survival (OS). Results: Overall 20584 patients were included in this study, with 4057 and 16527 patients receiving RP + ePLND and RT, respectively. After PSM, patients with RP + ePLND had similar CSS (5-year CSS rate: 97.8% vs. 97.2%, P=0.310) but longer OS (5-year OS rate: 96.0% vs. 90.8%, P<0.001) compared to those receiving RT. When separating RT cohort into external beam radiotherapy (EBRT) group and EBRT+ brachytherapy (BT) group, treatments with RP + ePLND and EBRT+ BT achieved equivalent OS and were both superior to EBRT alone (5-year OS rate: 96.0% vs. 94.4% vs. 90.0%, P<0.001). Subgroup analyses and multivariate analyses further confirmed the superiority of RP + ePLND and EBRT+ BT. Conclusion: RP + ePLND and EBRT + BT were associated with better survival outcomes compared to EBRT alone in PCa patients with a probability of LNI over 5%. However, no survival difference was observed between RP + ePLND and EBRT + BT.